Association between periodontitis and medication‐related osteonecrosis of the jaw: A systematic review and meta‐analysis. (3rd November 2019) - Lorenzo‐Pouso, Alejandro I.; Pérez‐Sayáns, Mario; Chamorro‐Petronacci, Cintia; Gándara‐Vila, Pilar; López‐Jornet, Pía; Carballo, Javier; García‐García, Abel
Abstract: Consensus has yet to be reached about the prevention and treatment of medication‐related osteonecrosis of the jaw (MRONJ), which is a treatment sequela of several antiresorptive therapies and other pharmaceutical interventions. Several epidemiologic studies have identified periodontal disease (PD) as a risk factor for this outcome. Thus, the objective of this systematic review and meta‐analysis was to investigate this association and its magnitude. A systematic search in MEDLINE via PubMed, Scopus and ISI Web of Science, and a meta‐analysis were undertaken. Observational studies that gathered information regarding prefixed definitions for both outcomes were selected, and the relevant information was then extracted, and their risk of bias was evaluated using the Newcastle‐Ottawa Scale. The protocol of the study was registered on PROSPERO (CRD42019125646). The initial search yielded 757 eligible records, of which 12 were deemed adequate for inclusion (5 cohort studies and 7 case‐control studies). On a random‐effects meta‐analysis, the risk of PD in MRONJ‐affected sites compared with at‐risk non‐affected patients was significantly greater, with a risk ratio of 2.75 (95% CI: 1.67‐4.52). Nonetheless, from a pooled analysis of three standardized periodontal measures (ie plaque index, clinical attachment loss and probing depth) no significant results were obtained. MRONJ appears to be associated with an increase in prevalence of PD. The direction of this association, and the factors influencing it must be investigated using further prospective data, and likewise, the possibility for using periodontal therapy as a prevention strategy must be looked into. Periodontal screening needs to be made an indispensable requisite for clinicians in order to establish a correct multidisciplinary approach in MRONJ.